Design and development of voltage reference for low voltage/low power circuits - Kang, Kheng Han. (2008)
Design a CMOS voltage reference circuit that can operate at 1-V power supply. The complete circuit block will be simulated, laid out and send for fabrication using the Austria Micro System (AMs) 0.6 CMOS N-well process.